Successful Pregnancy Outcome after Laparoscopic Cerclage in a Patient with Cervicovaginal Fistula - Giovanni Zanconato; Valentino Bergamini; Silvia Baggio; Elena Cavaliere; Massimo Franchi (Case Reports in Obstetrics and Gynecology)
Obstetric fistula usually originates from obstructed labor or, less often, from invasive maneuvers on the genital tract or the pregnant uterus. Overall, it is a rare finding in the obstetric practice of high income countries. In this report we describe the case of a successful term pregnancy in a patient with a history of recurrent late miscarriage due to a large cervical fistula of traumatic origin, connecting the uterine cavity and the posterior vaginal fornix. A combined approach of laparoscopic cerclage and transvaginal fistula repair effectively restored cervical competence and created the conditions for a viable birth in a subsequent pregnancy. This unusual cause of cervical incompetence may be included in the indications which benefit from an abdominal cerclage carried out as a minimally invasive procedure in the nonpregnant state.